Continuing Professional Education in Open Access - a French-German Survey - Oßwald, Achim; Schöpfel, Joachim; Jacquemin, Bernard (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2016)
While open access (OA) has become a significant part of scientific communication and academic publishing, qualification issues have been out of focus in the OA community until recent years. Based on findings about the qualification for OA within university-based programs in France and Germany the authors surveyed continuing professional education activities regarding OA in both countries in the years 2012-2015. The results indicate that there are different types of events qualifying for OA and reveal a lack of coherent concepts for different target groups. Until now traditional presentation formats have been dominant. Formats for distance learning, like MOOCs or webinars, might serve different needs and interests.